Whatever happened to my sister? - Ciraolo, Simona (Flying Eye Books : Published in the US by Nobrow (US) Inc., 2015)
"With sensitivity and graphic charm, Simona Ciraolo wonderfully explores a small child's bemusement at watching her old sibling grow up"--Page 4 of cover.